Persepsi Saksi-Saksi Yehuwa Tentang Pemberian Ulos Dalam Aktivitas Adat Batak Toba Di Tarutung - Claudia Irene Panggabean; Elisamark Sitopu; Elvri Teresia Simbolon (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Ngabang, 2024)
This research is motivated by the existence of an organization that does not accept or reject ulos in Toba Batak traditional activities, namely the Jehovah's Witnesses Tarutung congregation, where most of its members are people from the Toba Batak tribe. Jehovah's Witnesses in the Tarutung congregation have a different view from the non-Jehovah's Witness Toba Batak community regarding ulos. The aim of this research is to find out how Jehovah's Witnesses in the Tarutung congregation perceive the giving of ulos in Toba Batak traditional activities in Tarutung. This research uses a qualitative research method with the research approach used, namely the ethnographic research method. The data collection techniques used were observation, interviews and documentation. The results of the research show that Jehovah's Witnesses from the Tarutung congregation do not accept ulos in Toba Batak traditional activities because they view ulos as containing spiritual values that can bless human life and this is contrary to Biblical principles. However, Jehovah's Witnesses can receive or give ulos if it is simply given as a gift without having to give it in a manner that is in accordance with Batak customs. Jehovah's Witnesses in the Tarutung congregation have a good relationship with the community who receive ulos in Toba Batak traditional activities in Tarutung.